Klasa szkolna jako przestrzeń Innego - Ramik-Mażewska, Irena (Wydawnictwo Naukowe UAM, 2015)
In Pedagogy the world of values is widely understood as a range of upbringing processes that aim at changing the personality of a pupil. It does not concern the cognitive instrumental aspect, but mostly the development of an attitude of a person toward the world and other people, the development of views, attitudes, hierarchies of values, and life objectives. Therefore, one may find in that theoretical domain a place for Another. It is not however something very obvious. An existence of an appearance is a very distressing and daily phenomenon in the Polish school. The realization of aims in education and upbringing is an excuse for attempting different other activities. Educational institutions display the consent for integration of politics and economy and in so doing they agree on indicating what should be important and proper in the learning process. The consequence may be the incapacitation of schools (teachers) or institutions that take care of schools and the distortion of the process of upbringing, whose effect is more often pupils’ conformism.
Classroom as a Space for Another
Keywords: classroom; another; education